A Mathematical Model for Competition Between Local and Invasive Fish in Lake Poso, Indonesia - Tokonyai Tawanda Jonathan Rabvemhiri; Hajar; Juni Wijayanti Puspita; Dipo Aldila (The Indonesian Bio-Mathematical Society, 2026)
The introduction of Nile Tilapia into Lake Poso has created both ecological and economic challenges, particularly in its interaction with the endemic species Oryzias nigrimas. To understand the potential longterm impacts of this competition and the community’s economic use of Nile Tilapia, we introduced a novel mathematical model describing their population dynamics. The model is formulated as a four-dimension ordinary differential equations and analyzed for the positivity of solutions, existence and local stability of equilibrium points, and the influence of harvesting strategies. Numerical simulations, including bifurcation and time-series analyses, are conducted to assess the effects of constant and periodic harvesting of Nile Tilapia. The findings suggest that periodic harvesting can play a significant role in maintaining population balance and mitigating the ecological pressure on Oryzias nigrimas, offering insights for sustainable management of invasive fish in Lake Poso.